Evaluating the significance of exploratory practice as an approach to teacher development. Issue 4 (4th July 2018) - Soomro, Abdul Fattah
ABSTRACT: Exploratory practice (EP), as a framework for teacher development, is a collaborative endeavour of both teachers and learners which engages them in reflection to improve the quality of life in a language classroom. The present case study was carried out at the University of Sindh, Jamshoro (USJP) in Pakistan, where some teachers in the Institute of English Language and Literature volunteered to participate in the project by undertaking the principles of EP in their teaching. In this project, the researcher worked as both an EP practitioner and a teacher-consultant to a group of seven teachers at the USJP for a full academic year consisting of two semesters of four months each. The interviews were conducted twice during the project, first after Phase I from those who left the project halfway and a second time after the completion of Phase II from those who continued until the end to know the views of the participant-teachers about EP as an approach to their professional self-development. The findings show that teacher-participants found EP a practically viable option in their given circumstances and useful for their professional development as well as learning and teaching context in which they work.